THE EFFECT OF IMPLEMENTATION TEACHING FACTORY LEARNING MODEL ON STUDENTS INTEREST IN ENTREPRENEURSHIP IN CLASS XI FASHION MANAGEMENT AT STATE VOCATIONAL HIGH SCHOOL 6 YOGYAKARTA IN THE 2022/2023 ACADEMIC YEAR - Kuspranaji, Syifa Azzahra; Karyaningsih, Endang Wani; Inayah, Desy Tri (Prosiding Pendidikan Teknik Boga Busana, 2023)
This research aims to determine: The effect of implementing the teaching factory learning model on interest in entrepreneurship, the application of teaching factory learning model, and the interest in entrepreneurship of class This type of research is quantitative descriptive. The research sample with the Slovin formula at a significance level of 10% was obtained as many as 51 students. Collection data technique use questionnaires and documentation. The validity test uses Pearson product moment and showed that 1 item was declared invalid, so that 43 items were declared valid with a correlation value above 0.396. The instrument reliability test used Cronbach’s Alpha with coefficient values of 0.970 and 0.952. Data analysis technique uses the product moment correlation test, analysis prerequisite tests included normality test and linearity test. The research result show that: 1) the effect of implementing the teaching factory learning model on interest in entrepreneurship is 21.7%, 2) the application of teaching factory learning model is the moderate category with a relative frequency of 41.1%, and 3) Interest in entrepreneurship is in the high category with a relative frequency 54,9%.